The Effectivity of Bioinoculants on Suppressing Tylenchulus semipenetrans in Citrus Growing Soil in Cao Phong, Hoa Binh - Thu, Tran Thi Tuyet; Thi Thao, Nguye; Quang Phap, Trinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 4DO - 10.25073/2588-1094/vnuees.4433, 2019)
Tylenchulus semipenetrans causes serious damages related to decline on citrus in Cao Phong district, Hoa Binh province. This study evaluated the effects of EM, AMF, AT+Ketomium and Chitosan-Super in the control of nematodes. In the laboratory condition, the T.   semipenetrans was isolated from the soil and assessed for survival in the liquid medium containing EM and Chitosan-Super. The larval mortality rate reached 98.57% after 72 hours when using Chitosan-Super at 2% concentration. For pot experiments, T. semipenetrans and bioinoculants were infected into Hoa Binh red grapefruit rhizospheres. The results indicated that nematode density in the soil decreased the most in CT5 (Chitosan-Super), followed by CT4 (AT+Ketomium), CT3 (AMF+EM) and CT1 (AMF), CT2 (EM); nematode density in roots was the highest at CT5 of 132±27 individuals/5g of roots, while in CT1 there was no parasitic nematode on the red grapefruit root though its density in soil was high (2.424±125 individuals/250g of soil). Citrus grew normally in all of the experience formulas. Research results are an important basis for effective use of bioinoculants in preventing nematode parasitic on citrus.